Performance optimisation for visitor information systems using smart sensors and analysis of trial data. Issue 6 (1st November 2015) - Farnham, Tim
Abstract : Exploitation of smart sensor data has the potential to significantly improve the way in which content is wirelessly delivered to end user devices within visitor attractions. Content delivery over wireless infrastructure can use knowledge and predictions of performance for intelligently prefetching and adaptively exploiting opportunities in order to enhance the overall user experience. The advantage of this approach over prior static multicast and on‐demand approaches is that it is possible to exploit location awareness (such as using global positioning system, iBeacons) combined with accelerometer and compass and other sensors, to plan and adapt content delivery in a more efficient and flexible manner. This study assesses different options for prioritisation and prefetching of content over dedicated wireless fidelity off‐load infrastructure to compare the ability to satisfy the user demands. The overall assessment, based on trials performed at two visitor attractions, shows that intelligent predictive prefetching of content can greatly reduce the need for expensive infrastructure compared with alternative static reliable multicast or on‐demand delivery strategies.